Assessment of yam mild mosaic virus coat protein gene sequence diversity reveals the prevalence of cosmopolitan and African group of isolates in Ghana and Nigeria - Nkere, C.K.; Otto, E.; Atiri, G.I.; Onyeka, J.; Silva, G.; Bömer, M.; Seal, S.E.; Kumar, P. Lava (Elsevier, 2020)
This study analyzed the genetic diversity of 18 Yam mild mosaic virus (YMMV, genus Potyvirus) isolates collected from field surveys in Ghana (N = 8) and Nigeria (N = 10) in 2012−13. The full coat protein (CP) encoding region of the virus genome was sequenced and used for comparison and phylogenetic analysis of the YMMV isolates available in the NCBI nucleotide database. The mean nucleotide (nt) diversity was 13.4% among the 18 isolates (17 from D. alata and one from D. rotundata), 11.4% within the isolates of Ghana and 7.4% within the isolates of Nigeria. The phylogenetic clustering of the 18 YMMV isolates did not show correlation with the country of origin, and they aligned with the reference sequences of four of the 11 YMMV monophyletic groups representing the cosmopolitan group and the African group of YMMV isolates. High sequence homology of 99% between the YMMV sequence from Nigeria (CP12-DaN6-1) and a previously reported sequence from Togo (GenBank Accession Number AF548514) suggests a prevalence of seed-borne virus spread within the region. Understanding YMMV sequence diversity in West Africa aid in the improvement of diagnostic assays necessary for virus indexing and seed certification.